2008
DOI: 10.1111/j.1365-2214.2007.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and maternal risk factors for autism spectrum disorders in New South Wales, Australia

Abstract: Replication of risk factors from previous studies and a significant risk factor 'dose' effect add to growing evidence that maternal and perinatal factors are low magnitude risk factors for autism. The association between developmental disability and autism risk factors warrants further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 25 publications
3
76
0
4
Order By: Relevance
“…Studies also suggest a link between extreme prematurity and autism spectrum disorder (ASD), characterised by persistent deficits in social communication and social interaction, and restrictive and repetitive patterns of behaviours, interests or activities (10). Prematurity and low birth weight are considered to be risk factors for ASD (11)(12)(13)(14)(15)(16)(17). Two recent studies even found a gradual increased risk of traits of ASD with shorter gestation (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also suggest a link between extreme prematurity and autism spectrum disorder (ASD), characterised by persistent deficits in social communication and social interaction, and restrictive and repetitive patterns of behaviours, interests or activities (10). Prematurity and low birth weight are considered to be risk factors for ASD (11)(12)(13)(14)(15)(16)(17). Two recent studies even found a gradual increased risk of traits of ASD with shorter gestation (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…This data needs to be treated with caution as it is unknown whether or not these families were multilingual, which may have influenced the results. However, in an Australian study, mothers' country of birth being outside Australia was found to be a risk factor for autism [34].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple births have been associated with ASD according to a meta-analysis 157 as well as a cohort study, 176 whereas an ecological study did not find an association.…”
Section: Other Birth Characteristicsmentioning
confidence: 99%